Full body illusion is associated with widespread skin temperature reduction - Salomon, Roy; Lim, Melanie; Pfeiffer, Christian; Gassert, Roger; Blanke, Olaf (Frontiers in Behavioral Neuroscience, 2013)
A central feature of our consciousness is the experience of the self as a unified entity residing in a physical body, termed bodily self-consciousness. This phenomenon includes aspects such as the sense of owning a body (also known as body ownership) and has been suggested to arise from the integration of sensory and motor signals from the body. Several studies have shown that temporally synchronous tactile stimulation of the real body and visual stimulation of a fake or virtual body can induce changes in bodily self-consciousness, typically resulting in a sense of illusory ownership over the fake body. The present study assessed the effect of anatomical congruency of visuo-tactile stimulation on bodily self-consciousness. A virtual body was presented and temporally synchronous visuo-tactile stroking was applied simultaneously the participants’ body and to the virtual body. We manipulated the anatomical locations of the visuo-tactile stroking (i.e. on the back, on the leg), resulting in congruent stroking (stroking was felt and seen on the back or the leg) or incongruent stroking (i.e. stroking was felt on the leg and seen on the back). We measured self-identification with the virtual body and self-location as well as skin temperature. Illusory self-identification with the avatar as well as changes in self-localization were experienced in the congruent stroking conditions. Participants showed a decrease in skin temperature across several body locations during congruent stimulation. These data establish that the full-body illusion alters bodily self-consciousness and instigates widespread physiological changes in the participant’s body.